2015
DOI: 10.1089/dia.2015.0061
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Average Daily Risk Range as a Measure of Glycemic Variability in Youths with Type 1 Diabetes

Abstract: Objective: The Average Daily Risk Range (ADRR) is a measure of glycemic variability (GV) developed for adults with diabetes. Although the ADRR is increasingly being reported in pediatric diabetes research and may also be used in clinical management, it has never been examined for its sensitivity to predicting hyper-and hypoglycemia in youths or compared for its predictive ability with other measures of GV in youths. Thus, we present predictive validity data for the ADRR in youths with type 1 diabetes. Material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…For children, these metrics continue to perform in the hyperglycemic range, 1,6 and the LBGI works as designed in the hypoglycemic range as well ( Table 1 in Patton et al 1 ). However, according to this latest report, the predictive value of the ADRR may be weaker in the pediatric population.…”
Section: Fig 1 (A)mentioning
confidence: 99%
See 3 more Smart Citations
“…For children, these metrics continue to perform in the hyperglycemic range, 1,6 and the LBGI works as designed in the hypoglycemic range as well ( Table 1 in Patton et al 1 ). However, according to this latest report, the predictive value of the ADRR may be weaker in the pediatric population.…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…However, according to this latest report, the predictive value of the ADRR may be weaker in the pediatric population. 1 This may be due to artifacts in the study, such as the very low frequency of extreme low BG events (<40 mg/dL), which was 0.3% according to the text or 0.03% according to Table 2 in Patton et al 1 Statistically, it is natural to expect that low frequency of extreme hypoglycemia would result in nearzero correlation for metrics tuned to detect extreme hypoglycemia such as the ADRR; it is also normal that metrics taking into account all low BG values (e.g., the LBGI or the percentage of readings below a certain threshold) would perform better, as evidenced by Table 1 in Patton et al 1 Assuming, however, that the effect is real and is due to the specifics of the studied population, a correction of the ADRR may be in order for pediatric patients, and the metric may indeed require ''new guidelines.'' 6 Figure 1B presents a possible solution to this problem, derived from the basic definition of the BG scale transformation function.…”
Section: Fig 1 (A)mentioning
confidence: 99%
See 2 more Smart Citations
“…2 A description of various measures, with formulae used for their calculations, and a critical review of their limitations have been previously reported. 1,4 Risk-based GV measures are associated with frequency and severity of hypoglycemia, 5 while in vitro and in vivo data suggest that GV is as an independent risk factor for total mortality and death due to cardiovascular disease in both type 1 and type 2 diabetes. [6][7][8] The burden of hypoglycemia in adults with T1DM is significant and is associated with mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%